Ocena sprawności fizycznej studentów fizjoterapii po okresie pandemii Covid-19- badanie pilotażowe - Czechowska, Beata; Karbowiak, Marta; Stasiak, Piotr; Kuliś, Piotr; Siciński, Piotr; Motylewski, Sławomir (Kultura-Społeczeństwo-Edukacja, 2024)
Physical activity is one of key elements of a health-promoting lifestyle, and research confirms its impact on people’s health in both physical, social and emotional areas. In addition, it is an integral part of physioprophylaxis, by preventing or slowing down disease processes. The aim of this study was to assess selected motor characteristics and physical fitness of physiotherapy students. The study was based on selected physical fitness tests modelled on the International Physical Fitness Test. The study involved 140 students (94 females and 46 males), aged between 19 and 24 years. In the study conducted, we observed poorer performance of individual test attempts in women, while in men the mean scores of individual tests were within normal limits, except for the flexibility testt. The physical fitness of the physiotherapy students after the pandemic caused by the SARS-CoV-2 virus among the men is better than in the women and is within normal limits.